2021
DOI: 10.3390/molecules26082253
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin: Toxicity, Anticancer Activity and Analytical Procedures for Its Determination in Plant Seeds

Abstract: Amygdalin (d-Mandelonitrile 6-O-β-d-glucosido-β-d-glucoside) is a natural cyanogenic glycoside occurring in the seeds of some edible plants, such as bitter almonds and peaches. It is a medically interesting but controversial compound as it has anticancer activity on one hand and can be toxic via enzymatic degradation and production of hydrogen cyanide on the other hand. Despite numerous contributions on cancer cell lines, the clinical evidence for the anticancer activity of amygdalin is not fully confirmed. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 82 publications
1
37
0
2
Order By: Relevance
“…(2016) reported that sorghum grains also contain amygdalin. As other studies have not corroborated this observation (Pičmanová et al ., 2015; Thodberg et al ., 2018; Jaszczak-Wilke et al ., 2021), amygdalin production may be genotype-specific or stress induced. Further study is needed to identify other aldoxime derivatives in monocots.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) reported that sorghum grains also contain amygdalin. As other studies have not corroborated this observation (Pičmanová et al ., 2015; Thodberg et al ., 2018; Jaszczak-Wilke et al ., 2021), amygdalin production may be genotype-specific or stress induced. Further study is needed to identify other aldoxime derivatives in monocots.…”
Section: Discussionmentioning
confidence: 99%
“…The final products of amygdalin enzymatic hydrolyzation—benzaldehyde together with hydrogen cyanide—are responsible for the bitter aroma and flavor of amygdalin in fruit and result in said amygdalin toxicity and also affect the activity of pepsin when taken orally [ 25 , 26 ]. However, the cytotoxicity results of Choi and his team [ 27 ] showed that amygdalin alone was not toxic after incubation for 24 h but showed cytotoxicity in terms of the inhibition of cell proliferation, reactive oxygen species (ROS) generation, and induction of apoptosis ( Figure 2 ) only after β-glucosidase treatment.…”
Section: Amygdalinmentioning
confidence: 99%
“…Sahin et al (2011) and Sauer at el. (2015) reported that, in children aged 2 and 4, 500 mg of amygdalin caused vomiting, apathy, diarrhea, accelerated breathing, and a blood cyanide concentration of 163 µg/L [ 26 , 36 ]. In an adult woman, 9 g of amygdalin caused vomiting, dizziness, and a blood cyanide concentration of 143 µg/L [ 37 ].…”
Section: Amygdalinmentioning
confidence: 99%
“…Mostly these are ethanol, methanol, ethyl acetate, and water, but also 0.1% citric acid solution under reflux is used to increase the efficiency of extraction. To obtain a high-quality oil free of amygdalin, the extraction procedure should be optimized or cold-pressing can be carried out [22].…”
Section: Introductionmentioning
confidence: 99%